The Implementation on Using Google Classroom for Online Learning for Elementary School Teachers - Fiki Setiawan; Hery Prambudi; Pipin Supenah; Supriyatin Supriyatin (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2021)
The government has issued various policies to stop the spread of COVID-19. One of them is online learning (on the network) which is carried out by almost all levels of education in Indonesia. Learning models are developed based online (e-learning). Nevertheless, on the other hand, the implementation of online learning experiences obstacles such as teachers' lack of knowledge and skills in managing to learn online. This community service aims to improve the abilities and skills of elementary school teachers in using e-learning applications based on Google Classroom in helping the online learning process during the pandemic. The target of this activity is the Gegunung Village Elementary School teachers. Execution method using lectures, practicum, and question and answer. Training participants are given an understanding concept about distance learning media or online and practising use of the Google Classrooms application. The results of this activity include training participants very enthusiastic about participating in the training. The Gegunung Village Elementary School teacher can understand the use of google classroom with an indicator that the teacher can create online learning. The Gegunung Village Elementary School teachers have operated the application Google Classroom as an alternative medium. However, assistance still needs to be done until the teacher understands and uses Google Classroom as an online learning medium during the COVID-19 pandemic.